Menilai Kinerja Keuangan menggunakan Analisis Rasio Pada Koperasi Unit Desa (KUD) Sadar - Pancawati, Ni Luh Putu Anom (Valid: Jurnal Ilmiah, 2024)
Every business entity has achievements that are continuously evaluated related to the business operations carried out. The evaluation is carried out through financial performance analysis to obtain development information for each period related to the achievement of financial performance. This study aims to be able to provide an assessment of financial performance achievements using standard calculations of financial ratios obtained from financial statements from the period 2017 to 2021 at the Sadar Village Unit Cooperative (KUD). Evaluation of financial achievement is calculated by analyzing the ratio of liquidity, solvency, activity and profitability using financial ratios from the aspect of productivity and cooperative performance assessment based on the Regulation of the Minister of State of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 06/Per/M.KUKM/V/2006. The results showed that the liquidity ratio, namely the current ratio and cash ratio, showed unfavorable criteria, the solvency ratio of debt to total asset ratio and debt to equity ratio obtained a good category, the activity ratio consisting of receivable turn over and asset turn over was in the excellent criteria and the profitability ratio consisting of the Return On Asset ratio, Return On Equity was in the unfavorable criteria and Net Profit Margin was in a significant condition quite good and good. The ratio is one of the important considerations used for decision making and evaluating the performance carried out.